Impacts of climate change in a global hotspot for temperate marine biodiversity and ocean warming - Wernberg, T; Russell, B D; Moore, P J; Ling, S D; Smale, D A; Campbell, Alexandra H; Coleman, M A; Steinberg, P D; Kendrick, G A; Connell, S D (Journal of Experimental Marine Biology and Ecology, 2011)
Temperate Australia is a global hotspot for marine biodiversity and its waters have experienced well-above global average rates of ocean warming. We review the observed impacts of climate change (e.g. warming, ocean acidification, changes in storm patterns) on subtidal temperate coasts in Australia and assess how these systems are likely to respond to further change. Observed impacts are region specific with the greatest number of species responses attributable to climate change reported in south-eastern Australia, where recent ocean warming has been most pronounced. Here, a decline of giant kelp (Macrocystis pyrifera) and poleward range extension of a key herbivore (sea urchin) and other trophically important reef organisms has occurred. Although, evidence of changes on other coastlines around Australia is limited, we suggest that this is due to a lack of data rather than lack of change. Because of the east-west orientation of the south coast, most of Australia's temperate waters are found within a narrow latitudinal band, where any southward movement of isotherms is likely to affect species across very large areas. Future increases in temperature are likely to result in further range shifts of macroalgae and associated species, with range contractions and local extinctions to be expected for species that have their northern limits along the southern coastline. While there is currently no evidence of changes attributable to non-temperature related climate impacts, potentially due to a lack of long-term observational data, experimental evidence suggests that ocean acidification will result in negative effects on calcifying algae and animals. More importantly, recent experiments suggest the combined effects of climate change and non-climate stressors (overharvesting, reduced water quality) will lower the resilience of temperate marine communities to perturbations (e.g. storms, diseases, and introduced species), many of which are also predicted to increase in frequency and/or severity. Thus climate change is likely to, both by itself and in synergy with other stressors, impose change to southern Australian coastal species, including important habitat-forming algae and the associated ecological functioning of temperate coasts. Management of local and regional-scale stresses may increase the resistance of temperate marine communities to climate stressors and as such, provides an attractive tool for building resilience in temperate systems. © 2011 Elsevier B.V.